How do Middle School Student Trusts Predicted Moral Disengagement and Incivility? (Jurnal Bimbingan Konseling, 2020)
Trust becomes one of the important characters and part of the integrity character that must be possessed by students. The importance of trust can be seen from the many academic cheating behaviors committed by students such as plagiarism and cheating and their future behavior. This study uses a correlational design with cluster sampling data collection techniques by selecting 636 students (49.5% male, 50.5% female) junior high school in Semarang and Temanggung. Data retrieval is done with students filling the scale of academic integrity, moral disengagement and incivility. The results confirmed that moral disengagement and incivility negatively predicted student trust (R = 0.26, F(13,622) = 3.54, p < 0.01). This finding confirms that moral disengagement and incivility predict students' trust. Specifically the results of this study confirm that the type of moral disengagement is euphemistic labeling and the type of incivility is intentional incivility to predict student trust. Further discussion is discussed in this study.